2013
DOI: 10.1158/0008-5472.can-12-3292
|View full text |Cite
|
Sign up to set email alerts
|

PFI-1, a Highly Selective Protein Interaction Inhibitor, Targeting BET Bromodomains

Abstract: Bromo and extra terminal (BET) proteins (BRD2, BRD3, BRD4 and BRDT) are transcriptional regulators required for efficient expression of several growth promoting and anti-apoptotic genes as well as for cell cycle progression. BET proteins are recruited to transcriptionally active chromatin via their two N-terminal bromodomains (BRDs), a protein interaction module that specifically recognizes acetylated lysine residues in histones H3 and H4. Inhibition of the BET-histone interaction results in transcriptional do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
191
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(206 citation statements)
references
References 45 publications
10
191
0
3
Order By: Relevance
“…The in vivo data presented here and previous studies using other BETi have shown that inhibition of BET proteins is tolerated in mice (3,18,44,45). BETi exhibit broad transcriptional effects by targeting the general transcriptional elongation factor p-TEFb's interplay with Brd4.…”
Section: Discussionmentioning
confidence: 53%
“…The in vivo data presented here and previous studies using other BETi have shown that inhibition of BET proteins is tolerated in mice (3,18,44,45). BETi exhibit broad transcriptional effects by targeting the general transcriptional elongation factor p-TEFb's interplay with Brd4.…”
Section: Discussionmentioning
confidence: 53%
“…In accordance with the cell-cycle arrest observed at 24 to 48 hours, E2F1 target genes, but not E2F1 itself, are downregulated by both OTX015 and JQ1 (10), at a later time point than the effect on MYC or on TLR/JAK/STAT pathways. The high synergism reported in leukemia preclinical models with the combination of the BET bromodomain inhibitor PFI-1 with a pan-aurora kinase inhibitor (12) suggests that the combination of BET bromodomain inhibitors with drugs targeting the cell cycle might overcome the observed lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…8). Furthermore, BET bromodomain inhibitors have shown antitumor activity in different preclinical models derived from hematologic or solid tumors (4,5,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The compounds induce cell-cycle arrest in G 1 and, depending on the type of tumor model, apoptosis or cell differentiation (4,5,9,11,21).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of these cells to the potent pan-BET inhibitor PFI-1 (10, 35) led to significant reduction of recovery times of the photobleached nuclear region, suggesting efficient dissociation of BRD3 from chromatin ( Fig. 3), even at concentrations as low as 100 nM, given that the in vitro dissociation constant for this inhibitor is 80 nM for the BD1 of BRD3 and 76 nM for BD2 (35). At 250 nM, recovery times reached a plateau that did not decrease further at higher concentrations of the inhibitor.…”
Section: Rvx-208 Presents a Template For Bd2 Rearrangement Upon Bindingmentioning
confidence: 99%